2022
DOI: 10.26905/enjourme.v7i1.7978
|View full text |Cite
|
Sign up to set email alerts
|

Self-determination theory in teaching practice for higher education level

Abstract: This study aims to gain a deeper understanding of how self-determination theory is implemented in higher education. This review adheres to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) recommendations. The systematic review begins with an analysis of the identification procedure. Next, the best papers published between 2012 and 2022 were selected to explain how to compare significant aspects and efficient methods. The significance of self-determination theory to the evolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The third finding highlighted concerns about losing creativity, having a uniform writing style, and losing control over one's essay due to excessive dependence on AI. It contrasts with the optimism expressed in earlier research (Ariyanti, 2016;Rahayu et al, 2022). While these risks are significant, alternative explanations could be that these concerns stem from a lack of understanding of effectively using AI as a tool rather than a determinant of writing style (Davenport, 2018).…”
Section: Discussionmentioning
confidence: 86%
“…The third finding highlighted concerns about losing creativity, having a uniform writing style, and losing control over one's essay due to excessive dependence on AI. It contrasts with the optimism expressed in earlier research (Ariyanti, 2016;Rahayu et al, 2022). While these risks are significant, alternative explanations could be that these concerns stem from a lack of understanding of effectively using AI as a tool rather than a determinant of writing style (Davenport, 2018).…”
Section: Discussionmentioning
confidence: 86%
“…Specifically, the study builds upon theoretical concepts that provide a foundation for the effective application of gamification mechanics (Hamari et al, 2014;Kim et al, 2017). These theoretical frameworks include selfdetermination theory (Cherry, 2022;Noels et al, 2019;Rahayu et al, 2022), flow theory (dos Santos et al, 2018;Vann & Tawfik, 2020), behaviorism (Al-Dosakee & Ozdamli, 2021Budiman, 2017;Figueroa Flores, 2015), and cognitive load theory (Ragsdale, 2019;Sweller, 2017;Turan et al, 2016). By demonstrating the positive impact of incorporating gamified chatbot-driven sessions on student motivation, engagement, and language proficiency, this study provides empirical support for the effectiveness of these theoretical frameworks in practical language learning contexts.…”
Section: Results Obtained From the Survey On Students' Attitudes Towa...mentioning
confidence: 99%
“…Future research could delve deeper into these alternative explanations by examining how individual attitudes towards technology influence self-determination factors and exploring how different instructional designs may affect learner perceptions within digital classrooms. Limitations include the focus on only two universities within Indonesia, which may limit generalizability across different contexts or institutions; however, comparison with similar studies suggests trends may hold more broadly across the Indonesian higher education sector (Rahayu et al, 2022). Furthermore, while we used a mixed-methods approach combining quantitative survey data and qualitative interview data, self-reported measures can sometimes be susceptible to bias.…”
Section: Discussionmentioning
confidence: 99%
“…Self-determination theory (SDT), a psychological framework proposed by (Ryan & Deci, 2017), suggests that human motivation and personal growth are intrinsically linked to three basic psychological needs: autonomy (the need to control one's actions), competence (the need to master tasks), and relatedness (the need for social interaction). Numerous studies conducted within traditional classroom-based education settings have confirmed SDT's effectiveness in fostering student motivation, leading to improved academic performance (Alrabai, 2021;Rahayu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%